Evidence for orbitally controlled size variations of the East Antarctic Ice Sheet during the late Miocene - Grützner, J.; Rebesco, M.A.; Cooper, A.K.; Forsberg, C.F.; Kryc, K.A.; Wefer, G. (Geology, 2003)
Ocean Drilling Program Site 1165 penetrated drift sediments on the East Antarctic continental rise and recovered sediments from a low-energy depositional environment. The sediments are characterized by prominent alternations between a green to greenish-gray diatom-bearing hemipelagic facies and gray to dark gray hemiturbiditic facies. Our investigation of an upper Miocene section, using high-resolution color spectra, multisensor core logs, and X-ray fluorescence scans, reveals that sedimentation changes occur at Milankovitch orbital frequencies of obliquity and precession. We use this finding to derive an astronomical calibrated time scale and to calculate iron mass-accumulation rates, as a proxy for sediment-accumulation rates. Terrigenous iron fluxes change by as much as 100% during each obliquity cycle. This change and an episodic pattern of enhanced ice-rafted debris deposition during times of deglaciation provide evidence for a dynamic and likely wet-based late Miocene East Antarctic Ice Sheet (EAIS) that underwent large size variations at orbital time scales. The dynamic behavior of the EAIS implies that a significant proportion of the variability seen in oxygen isotope records of the late Miocene reflects Antarctic ice-volume changes.
Keywords: Antarktis; Sørishavet; geologi; glasiologi; maringeologi; paleoklimatologi

Utfordringene for legene ved polarekspedisjoner omkring år 1900 - Albretsen, Carl Severin (Tidsskrift for den Norske Laegeforening, 2003)
Keywords: Antarktis; medisin; polarkespedisjoner

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

The Late Pleistocene and Holocene Glacial and Climate History of the Antarctic Peninsula Region as Documented by the Land and Lake Sediment Records- A Review - Hjort, Christian; Ingólfsson, Ólafur; Bentley, Michael J; Björck, Svante (Antarctic Peninsula Climate Variability: Historical and Paleoenvironmental Perspectives, 2003)
This chapter contains sections titled: Introduction Methods Glaciation History and the Raised Marine Shorelines Mid-Holocene Glacial Readvances The Holocene Climatic Optimum Neoglaciation and the Little Ice Age Discussion and Conclusions
Keywords: Antarktis; glasiologi; paleoglasiologi; sedimentologi

Glacial and Climate History of the Antarctic Peninsula since the Last Glacial Maximum - Ingólfsson, Ólafur; Hjort, Christian; Humlum, Ole (Arctic, Antarctic, and Alpine Research, 2003)
During the Last Glacial Maximum (LGM), ice thickened considerably and expanded toward the outer continental shelf around the Antarctic Peninsula. Deglaciation occurred between >14 ka BP and ca. 6 ka BP, when interglacial climate was established in the region. Deglaciation of some local sites was as recent as 4?3 ka BP. After a climate optimum, peaking ca. 4?3 ka BP, a distinct climate cooling occurred. It is characterized at a number of sites by expanding glaciers and ice shelves. Rapid warming during the past 50 yr may be causing instability of some Antarctic Peninsula ice shelves. Detailed reconstructions of the glacial and climatic history of the Antarctic Peninsula since LGM are hampered by scarcity of available archives, low resolution of many datasets, and problems in dating samples. Consequently, the configuration of LGM ice sheets, pattern of subsequent deglaciation, and environmental changes are poorly constrained both temporally and spatially.
Keywords: Antarktis; glasiologi; klimaendringer; marin geologi; paleoklimatologi

Blant pelssel og pingvinar. Ei julereise til Sør-Georgia og Antarktis - Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2003)
Keywords: Antarktis; cruiseturisme; dagbøker; polareksspedisjoner; reisebeskrivelser; reiseskildringer

The making and unmaking of a supercontinent: Rodinia revisited - Meert, Joseph G.; Torsvik, Trond H. (Orogenic Belts, Regional and Global Tectonics: A Memorial Volume to Chris McAulay Powell, 2003)
During the Neoproterozoic, a supercontinent commonly referred to as Rodinia, supposedly formed at ca. 1100 Ma and broke apart at around 800–700 Ma. However, continental fits (e.g., Laurentia vs. Australia–Antarctica, Greater India vs. Australia–Antarctica, Amazonian craton [AC] vs. Laurentia, etc.) and the timing of break-up as postulated in a number of influential papers in the early–mid-1990s are at odds with palaeomagnetic data. The new data necessitate an entirely different fit of East Gondwana elements and western Gondwana and call into question the validity of SWEAT, AUSWUS models and other variants. At the same time, the geologic record indicates that Neoproterozoic and early Paleozoic rift margins surrounded Laurentia, while similar-aged collisional belts dissected Gondwana. Collectively, these geologic observations indicate the breakup of one supercontinent followed rapidly by the assembly of another smaller supercontinent (Gondwana). At issue, and what we outline in this paper, is the difficulty in determining the exact geometry of the earlier supercontinent. We discuss the various models that have been proposed and highlight key areas of contention. These include the relationships between the various ‘external’ Rodinian cratons to Laurentia (e.g., Baltica, Siberia and Amazonia), the notion of true polar wander (TPW), the lack of reliable paleomagnetic data and the enigmatic interpretations of the geologic data. Thus, we acknowledge the existence of a Rodinia supercontinent, but we can place only loose constraints on its exact disposition at any point in time.
Keywords: Antarktis; Dronning Maud Land; geologi; paleogeografi

Moment Magnitude Determination for Local and Regional Earthquakes Based on Source Spectra - Ottemöller, Lars; Havskov, Jens (Bulletin of the Seismological Society of America, 2003)
We investigated the use of an automated routine to determine moment magnitudes from the displacement spectra of local and regional earthquakes. Two algorithms, a genetic algorithm and a converging grid search, were developed and tested with earthquake data from Mexico, Norway, and Deception Island (Antarctica). It was found that compared with manual analysis, the algorithms give reliable automatic moment magnitude (Mw) estimates in the range -1 < M < 8. The converging grid search appeared to be more cost-effective than the genetic algorithm. Mw at local and regional distances seems superior to amplitude-based magnitudes that saturate for large earthquakes. The application of the automated algorithm in near real time may help to obtain a nonsaturated magnitude estimate in the case of a large earthquake immediately after the earthquake has occurred. Also, the method can be useful for processing large amounts of data.
Keywords: Antarktis; Deceptionøya; Sør-Shetlandsøyene; seismologi

Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

Sea ice formation on a very cold surface - Smedsrud, Lars Henrik; Saloranta, Tuomo; Haugan, Peter M; Kangas, Tor-Villy (Geophysical Research Letters, 2003)
In this study laboratory experiments of sea ice formed on a vertical surface with initial temperature of −30 to −50°C are presented. The ice formation is rapid, and in 300 s >5 mm of sea ice is formed. Ice formation cooled and salinified the water, and induced a vertical down wards flow of ∼5 mm/s with a boundary layer about 5 mm thick. This ice has a structure with columnar crystals that have small circular cross sections (0.2–1.0 mm) and sea ice salinities are between 24 and 32. A simple model approach indicate that the thermal conductivity of such ice is lower than for other types of sea ice.
Keywords: Antarktis; geofysikk; glasiologi; havis; innlandsis; isshelf; laboratorieeksperimenter; polarområdene; sjøis